Diagnostic value of the combined detection of serum tumor necrosis factor-α and fecal calprotectin in early sepsis-related encephalopathy - Chenghong OuYang; ChunLi Yang; Qi Wu; Fang Liu; Zhenhuan Chen (Frontiers in Medicine)
ObjectiveTo investigate the value of tumor necrosis factor-α (TNF-α) and fecal calprotectin in the early diagnosis and prognosis of sepsis-associated encephalopathy (SAE).MethodsWe recruited 150 patients with sepsis, admitted from January 2020 to January 2022. Of these, 80 patients had SAE and 70 patients did not. The levels of serum TNF-α and fecal calprotectin of patients while in the intensive care unit were measured and correlated with the acute physiology and chronic health evaluation scoring system II (APACHE II) score, the sequential organ failure assessment (SOFA) score and 28-day mortality. We examined the value of TNF-α and fecal calprotectin in the diagnosis and prognosis of SAE.ResultsThe APACHE II and SOFA scores and 28-day mortality of the SAE group were significantly higher than those of the sepsis group, which indicated that the condition of the SAE group was more critical. In the SAE group, TNF-α and fecal calprotectin levels were positively correlated with the APACHE II and SOFA scores (P < 0.05), which may be related to disease severity. Assessing TNF-α level alongside fecal calprotectin level is highly valuable for the diagnosis of SAE and determining poor prognoses in SAE patients.ConclusionsTNF-α and fecal calprotectin may be involved in the pathogenesis of SAE. Both have high specificity and sensitivity for early SAE diagnosis. Moreover, they have good predictive value and can serve as prognostic indicators.